Criminal infringement of environmental planning violations - Baraa, Munther Kamal Abdul Latif; Sura, Hatem Majeed Abdul Latif (Revue jurisprudence; Vol 11 No 02 (2019): مجلة الاجتهاد القضائي, 2019)
Urban planning plays an important role in sustainable development processes, which are increasingly dependent on development and development of the environment to advanced levels by helping to create a vibrant public situation. The study of architecture and urban planning in particular is an art and science and the latter requires knowledge and knowledge of various aspects related to the emergence of architecture and its development and development throughout history, especially the elements of space and time and their reflection on the cultural and environmental dimensions of architecture. Societies always need controls and legislation to regulate their affairs and to arrange relations between individuals. Perhaps these values ​​are the same, which form the common denominators between individuals and groups, which are similar to the concept of society, which advances these legislations and moves towards urbanization, development and prosperity. The legislation on urban planning almost combines the development of rules and regulations for the planning of residential areas, taking into account the protection of the environment. Therefore, it is necessary in this study to identify the laws, regulations and instructions that determine the importance of urban planning between the pros and cons of these legislations in order to come up with a comprehensive vision and specific recommendations on this legislation, noting that many of the architectural problems facing Arab society today in the field of its built environment are result The absence of legislation capable of simulating all the requirements of development to meet the aspirations.